Prognosis of Tyrosine Kinase Inhibitor Therapy for Non-Small Cell Lung Cancer - Agus Andreas Santoso; Suryanti Dwi Pratiwi; Yani Jane Sugiri; Harun Al Rasyid; Aditya Sri Listyoko (Jurnal Respirasi)
Introduction: Non-small cell lung cancer (NSCLC) was the primary cause of death in lung cancer. Tyrosine kinase inhibitors (TKIs) were one of the management options for NSCLC. Meanwhile, serum carcinoembryonic antigen (CEA) plays a crucial role in the diagnosis and prognosis of NSCLC patients. This study aimed to determine the effectiveness of epidermal growth factor receptor (EGFR)-TKI based on progression-free survival (PFS) and overall survival (OS) in NSCLC patients with common EGFR mutations.